Chemical characteristics and volatile compounds profiles in different muscle part of the farmed hybrid catfish (Clarias macrocephalus × Clarias gariepinus). (1st November 2021) - Phetsang, Hatairad; Panpipat, Worawan; Panya, Atikorn; Phonsatta, Natthaporn; Cheong, Ling‐Zhi; Chaijan, Manat
Summary: The chemical characteristics and volatile compounds profiles in distinct anatomical sites of a farm‐raised hybrid catfish ( Clarias macrocephalus  ×  Clarias gariepinus ) were investigated. Total haem proteins, trimethylamine‐nitrogen, TBARS, n ‐9 oleic acid, n ‐6 linoleic acid and total concentration of all volatile compounds were all higher in the lateral line with the maximum redness index (p < 0.05). Dorsal muscle lipid contained more eicosapentaenoic acid and docosahexaenoic acid than the other two muscles (p < 0.05). Ventral muscle exhibited the highest fat content (p < 0.05) and was the only muscle discovered to have n ‐3 linolenic acid. Geosmin and 2‐methylisoborneol (2‐MIB) were found in all three muscles. Despite the fact that 2‐MIB and geosmin are lipophilic compounds, their distribution was unaffected by fat content, with the highest levels in the lateral line (p < 0.05). Odour activity values (OAV) and sensory analyses revealed that not only 2‐MIB and geosmin but also ( E )‐2‐nonenal and 1‐octen‐3‐ol, intensified the earthy and muddy odour in catfish muscles. The total off‐odour of catfish muscles was influenced by n ‐9 oleic acid and n ‐6 linoleic acid, according to the correlation analysis. The off‐odour compounds had a substantial negative connection with total n ‐3 PUFA, as well as the irrelevance with fat content, according to this study. Abstract : Chemical indices and volatile compounds of fresh hybrid catfish were affected by muscle location. The results can be used to develop post‐mortem handling and processing criteria to address off‐flavour issues and increase the market value of farmed hybrid catfish.